1993
DOI: 10.1007/bf02251202
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of undernutrition in Parkinson's disease and its relationship to clinical disease parameters

Abstract: An anthropometric study was performed in 95 subjects (53 male, 42 female) with Parkinson's disease. Weight, height, triceps and biceps skin-fold thicknesses, and mid-arm circumference were recorded. A high incidence of undernutrition was found (23.6% of males and 22.5% of females, as defined by recent British guidelines). A subgroup of severely disabled patients with Parkinson's disease had a significantly lower mean body mass index than a similarly disabled control group with chronic pyramidal upper motor neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
83
5
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 8 publications
7
83
5
8
Order By: Relevance
“…All the previous studies have reported lower mean BMIs than the mean values we found in this study (men 23.0 -25.4 vs 27.0 kg=m 2 ; women 22.0 -22.6 vs 26.9 kg=m 2 ; both sexes together 23.5 -24.4 vs 27.0 kg=m 2 ; Markus et al, 1993;Beyer et al, 1995;Durrieu et al, 1992;Jankovic et al, 1992). Also the proportion of overweight patients was lower than in our study (20 -30% vs 62%) (Markus et al, 1993;Abbott et al, 1992).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…All the previous studies have reported lower mean BMIs than the mean values we found in this study (men 23.0 -25.4 vs 27.0 kg=m 2 ; women 22.0 -22.6 vs 26.9 kg=m 2 ; both sexes together 23.5 -24.4 vs 27.0 kg=m 2 ; Markus et al, 1993;Beyer et al, 1995;Durrieu et al, 1992;Jankovic et al, 1992). Also the proportion of overweight patients was lower than in our study (20 -30% vs 62%) (Markus et al, 1993;Abbott et al, 1992).…”
Section: Discussioncontrasting
confidence: 76%
“…Also the proportion of overweight patients was lower than in our study (20 -30% vs 62%) (Markus et al, 1993;Abbott et al, 1992). However, the difference versus normal controls was not always statistically significant.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…L -dopa has also been implicated in weight loss via a lypolitic effect [32] . Several other hypothesis have been proposed including a decrease of food intake, loss of appetite, decreased nutrient absorption, hypothalamic dysregulation, depression, use of neuroleptics, nausea and anorexia (the latter two as side effects of antiparkinsonian medication) [33][34][35][36] . Therefore, it could be suggested that WG following DBS could only be a homeostatic response of the body in those who had lost weight during the course of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have found that severe dyskinesias can contribute to weight loss, 1003 others have not found this association. 1002 It is also important to recognize that the weight loss that occurs in PD may result from patients receiving higher dosages of levodopa per unit of body mass, which tends to aggravate dyskinesia, thereby setting up a vicious cycle.…”
mentioning
confidence: 97%